Measuring Positive Youth Development in Malaysia - Mahadzirah, Mohamad; Morliyati, Mohammad (2014)
The main purpose of this study was to identify the underlying factors that measured positive youth development among Malay youths in Malaysia. This is to ensure that youth development programmes would be developed based on the aspects of positive youth development identified in this study. Data was collected at youth programmes organised by the Ministry of Youth and Sport, Malaysia using self- administered questionnaires among Malay youths. A total of 431 youths were involved in this study, comprising 204 males and 227 females. Structural equation modelling (SEM) was used to analyse the data. The respondents were selected using a two-step sampling technique starting with an area sampling and followed by a systematic sampling. The findings of the study suggest that the measurement model of positive youth development was valid, reliable and achieved an acceptable level of goodnessof-fit. The findings also suggest that there are four underlying factors that measured positive youth development, identified as self-determination, self- competence, prosocial norms and bonding. These factors are aspects of positive youth development that require emphasis in youth development programmes to ensure sustainable youth development that would give benefits to individuals, and contribute to the wellbeing of the society and prosperity of the nation.